Reversible cerebral vasoconstriction syndrome developed during treatment of Parkinson's disease with rasagiline mesylate: A case report - Akihiko Nakaya; Kimihiko Kaneko; Arifumi Matsumoto; Yuki Matsumoto; Yasuhiko Matsumori; Isao Nagano (SAGE Publishing, 2024)
Background Rasagiline mesylate, a monoamine oxidase-B inhibitor, is used in Parkinson's disease (PD) treatment. We report a case of reversible cerebral vasoconstriction syndrome (RCVS) developed after rasagiline mesylate initiation. Case presentation A 59-year-old woman was diagnosed with PD at the age of 54 years. She experienced frequent episodes of nausea after increasing the dose of levodopa-carbidopa hydrate, and her nausea worsened with the addition of rasagiline mesylate. Three months later, the patient experienced recurrent thunderclap headaches. Brain imaging revealed subarachnoid hemorrhage with segmental vasoconstriction in the main trunks of multiple cerebral arteries. The subsequent clinical course was consistent with RCVS. Her headache and nausea were completely resolved by the discontinuation of rasagiline mesylate and addition of verapamil hydrochloride. Discussion Worsened nausea was the only sign implicating the elevated monoamine levels, potentially linked to the development of RCVS. RCVS should be considered when a patient taking rasagiline mesylate experiences thunderclap headache.